Evaluating Elements Influencing Student Engagement: An Analysis Utilizing Multiple Regression - Saraswathi Meena, R.; Narmadha, R.; Tejaswini, P. K.; Saravana Kumar, M. (Journal of Engineering Education Transformations, 2025)
"Exploring Student Engagement: A Comprehensive Multiple Regression Analysis" delves into the intricate interplay of factors influencing student engagement, focusing on variables such as class size, study hours, teaching style, class hours, and technology use. Conducted in a diverse educational setting with undergraduate students from urban and suburban areas, including a significant proportion of first-generation college students, this study employed extensive data collection and analysis. The results revealed significant correlations between these factors and engagement levels, offering actionable insights for educators. The findings underscore the critical influencers of engagement, facilitating targeted improvements in teaching practices and classroom environments. This approach equips educators with knowledge about effective interventions, enabling them to assess their impact and tailor strategies to individual student needs. By doing so, the study aims to enhance overall learning outcomes, offering a valuable framework for fostering student engagement through informed, evidence-based educational practices, thus significantly contributing to the academic success of diverse student populations.